ОПТИМАЛЬНА РЕКОНФІГУРАЦІЯ РОЗПОДІЛЬНОЇ ЕЛЕКТРИЧНОЇ МЕРЕЖІ - Циганенко, Б.В. (Інститут електродинаміки НАН України, Київ, 2016)
The problems associated with the operation of power distribution systems with voltage 6-35 kV are investigated. The urgency of the implementation of Smart Grid technology in the decentralized management of the distribution network modes. Formed objective function optimal configuration of the radial electric network. The mathematical model of optimal distribution network configuration function, adapted to the apparatus of the genetic algorithms theory are presented. References 7.